Inhibition of miR-15a-5p Promotes the Chemoresistance to Pirarubicin in Hepatocellular Carcinoma via Targeting eIF4E - Ying Zhang (Hindawi Limited, 2021)
Chemoresistance has become a primary hurdle in the therapeutic outcome of hepatocellular carcinoma. Substantial evidences have demonstrated that microRNAs (miRNAs) are closely associated with the chemoresistance of hepatocellular carcinoma (HCC). Our investigation is aimed at testifying the influence of microRNA-15a-5p (miR-15a-5p)/eukaryotic translation initiation factor 4E (eIF4E) on hepatocellular carcinoma resistance to pirarubicin (THP). In our study, miR-15a-5p expression was increased in THP-treated HepG2 cells. Downregulation of miR-15a-5p blocked cell growth and elevated cell apoptosis of HepG2 cells treated with THP. Moreover, eIF4E was verified as a direct target of miR-15a-5p by binding its 3′-UTR, which was confirmed by luciferase report experiment. Additionally, eIF4E was negatively associated with the miR-15a-5p expression in HepG2 cells. Mechanically, eIF4E was proven as a specific downstream of miR-15a-5p and mediated the effects of miR-15a-5p on cell viability and apoptosis of HepG2 cells treated with THP. These findings supported that miR-15a-5p facilitated THP resistance of hepatocellular carcinoma cells by modulating eIF4E, thus providing an experimental basis that miR-15a-5p might act as a novel diagnostic target in hepatocellular carcinoma resistance to THP.